2006
DOI: 10.1177/1468796806070718
|View full text |Cite
|
Sign up to set email alerts
|

Language Politics and Regional Nationalist Mobilization in Galicia and Wales

Abstract: Marshaling original data from surveys and interviews with regional nationalist party activists, this article compares language politics in two ‘stateless’ European nations with strong regional identities: Galicia (Spain) and Wales (UK). In Galicia, where the regional language is widely spoken, the nationalist party places significant emphasis on language-related issues. Yet in Wales, despite the minority status of Welsh, the political arm of the nationalist movement assumes a restrained stance toward the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Whilst some authors point to the destructive effects of diglossia in leading successively fewer people to speak a language (Davies ; Drakeford and Lynn ; Lindsay et al ; Roberts and Paden ; Trask ; van Morgan ), others point to its constructive influence in creating the conditions for the emergence and nurturing of a linguistically centred ethnic identity. Thus, even though between 1801 and 1991 the national census in the United Kingdom suggested that the population of Wales having some ability in the Welsh language fell from 80% to 18.7% (Higgs et al ), an often cited assertion is that Welsh people, unlike the Scottish or Irish people, have retained a highly developed sense of nationhood linked to their language.…”
Section: Background Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst some authors point to the destructive effects of diglossia in leading successively fewer people to speak a language (Davies ; Drakeford and Lynn ; Lindsay et al ; Roberts and Paden ; Trask ; van Morgan ), others point to its constructive influence in creating the conditions for the emergence and nurturing of a linguistically centred ethnic identity. Thus, even though between 1801 and 1991 the national census in the United Kingdom suggested that the population of Wales having some ability in the Welsh language fell from 80% to 18.7% (Higgs et al ), an often cited assertion is that Welsh people, unlike the Scottish or Irish people, have retained a highly developed sense of nationhood linked to their language.…”
Section: Background Considerationsmentioning
confidence: 99%
“…The success of a ‘minority language’ project or ethnolinguistic identity, however, rests not only on the number of speakers but on the ability of a language group to discursively suppress its heterogeneity and to imagine its speakers as having a collective identity (van Morgan ). A new social order of Welsh social and cultural life, however, presages some likely changes in the meaning and relevance of being ‘Welsh speaking’ for Welsh speakers, and arguably new challenges in promoting a collective linguistic identity.…”
Section: Background Considerationsmentioning
confidence: 99%
“…As well as asserting the importance of specific attributes (e.g., language), members of ethnolinguistic minorities often engage in campaigns aimed at achieving specific political goals, such as greater official recognition of or autonomy for the in‐group, that would benefit from a support base defined as broadly as possible (van Morgan, 2006). This is the case in Wales, where Plaid Cymru – the main nationalist party – campaigns for greater political autonomy for Wales, with the ultimate aim of Welsh national self‐government.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these goals are clearly identity relevant and identity contingent, particularly in how they draw on the notion of a distinctive Welsh national identity as a reason for pursuing the goal of political autonomy. Yet, while there is evidence of a connection between language fluency and support for group autonomy at a broad, sociological level (e.g., Balsom, 1985; van Morgan, 2006), the identity‐related processes underlying it remain under‐researched (van Morgan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…8 More information about the political importance of language in Spain may be found in Van Morgan (2006), who investigates the impact of linguistic grievances on nationalist mobilisation in Galicia. For an insightful ecological analysis of the effects of language on voting in Catalonia, see Gutiérrez (2014).…”
mentioning
confidence: 99%